Valores e estrutura social no Brasil - Felix Garcia Lopez; Fabio de Sá e Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper addresses the relationship between social structure and social values in the Brazilian society in light of survey data from a national sample of 3,772 respondents. In addition to examining traditional variables - such as income and education -, the analysis incorporated information on variables such as sex, race/ethnicity, age, geographic region, and religious affiliation. The survey questions dealt with issues such as adherence to democracy, acceptance of diversity, gender equality, reasons for inequality, and others. The results were ambivalent. While presenting different degrees of effect according to the questions and issues, education and age emerged as key variables to explain the substantive differences in the responses. The youth, in particular, presents levels of adherence to democratic principles and values that are higher than others. Interestingly, none of the differences is explained by income, which suggests the lack of a "new middle class" holding different values when one assumes hat ranges of income are the main indicators of "social classes", as it has become a commonplace in contemporary debates.
Keywords: H5; H53; 330; social structure in Brazil; social values; class structure; democracy in Brazil; new middle class